Development of latex-based as new coagulant for industrial coolant wastewater treatment / Ku Halim Ku Hamid and Salina Abdul Rahman - Ku Hamid, Ku Halim; Abdul Rahman, Salina (2002)
In recent years, polymer application has become more important in wastewater treatment due to easier sludge disposal, reduction in cost for chemical consumption and increase pollutant removal efficiencies. It can be used either as coagulant or coagulant aid to destabilize and aggregate colloidal particles. In this study, industrial coolant wastewater was treated with latex-based material as a new coagulant. Latex is a liquid particle of rubber in an aqueous serum containing various kinds of organic and inorganic substances. It can be coagulated by adding acetic acid (1 %) or formic acid (0.5 %). Composition of latex are varies depending upon botanical species and influenced by biological and climate. Characteristic of the industrial coolant wastewater was determined before and after the treatment. It was found that COD of the wastewater was reduced to 99.9 percent and comply the Environmental Standard to be discharged to the monsoon drain after polishing with commercial grade of activated carbon and dilution process.